Legitimate Mail Sender Verification and Flood Attack Detection Using Java Networking and Swing UI - Sinchana K R,; Prof Dr. H P Mohan Kumar, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
With the growing prevalence of cyber threats, securing email communication is essential. This paper presents a Legitimate Mail Sender Verification and Flood Attack Detection System developed using Java Networking and Swing UI. The system comprises client and server modules, enabling user registration, authentication, and secure email exchange. To ensure sender legitimacy, email bodies are encrypted using AES, and MD5 hashes are used for signature verification. The server records the sender’s IP address and prompts users to validate it. A mismatch results in sender blocking. On the receiver's end, signature validation confirms message integrity. Any inconsistency flags the message as a flood attack. Additionally, a simulated attacker module allows testing by modifying messages mid-transit, aiding in real-time detection. This approach integrates encryption, digital signature validation, and IP tracking to protect against spoofing, tampering, and denial-of-service threats in email systems.